2012
DOI: 10.1002/rcm.6358
|View full text |Cite
|
Sign up to set email alerts
|

On‐plate deposition of oxidized proteins to facilitate protein footprinting studies by radical probe mass spectrometry

Abstract: The on-plate deposition of oxidized proteins is described to advance footprinting applications by radical probe mass spectrometry (RP-MS). An electrospray ionization (ESI) needle assembly mounted vertically over a 384-target matrix-assisted laser desorption/ionization (MALDI) plate enabled the limited oxidation of proteins as they were released in the charged droplets ahead of their deposition on the plate. This method combined with on-plate proteolytic digestion protocols expedites the analysis of proteins ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It has been previously demonstrated that the footprinting rate k fp determined from synchrotron radiolysis experiments has a qualitative correlation with local solvent accessibility (8,31,(37)(38)(39). A similar correlation was also observed in other measurements with hydroxyl radicals generated from either electrical discharge (40) or lasers (14,41,42). From a quantitative perspective, however, such a comparison is still insufficient, given that only identical segments could be compared across different conformational states.…”
Section: Strong Correlation Between Hrf-based Pfs and Structural Propertiesmentioning
confidence: 60%
“…It has been previously demonstrated that the footprinting rate k fp determined from synchrotron radiolysis experiments has a qualitative correlation with local solvent accessibility (8,31,(37)(38)(39). A similar correlation was also observed in other measurements with hydroxyl radicals generated from either electrical discharge (40) or lasers (14,41,42). From a quantitative perspective, however, such a comparison is still insufficient, given that only identical segments could be compared across different conformational states.…”
Section: Strong Correlation Between Hrf-based Pfs and Structural Propertiesmentioning
confidence: 60%
“…22 On the other hand, higher spray voltage will result in more vigorous CD, based on which Downard's group have done intensive proteomics-related research. [31][32][33] Therefore, the results indicated that a more sever CD through raising spray voltage or using metal spray emitter facilitated the formation of Mc À ions.…”
Section: Effect Of Experimental Parameters On Dcbq Reductionmentioning
confidence: 86%
“…The electrical discharge approach has been exploited in numerous studies of proteins and their interactions, including investigations of the impact of sustained oxidation of these proteins and complexes of significance to oxidative damage in disease pathogenesis. It has also been implemented in conjunction with the deposition of samples onto a large format matrix‐assisted laser desorption/ ionisation (MALDI) plate to aid high‐throughput analysis.…”
mentioning
confidence: 99%
“…This results in the production of hydroxyl radicals within the solution at the needle tip, such that the electrosprayed droplets release oxidised protein in addition to its unmodified counterpart. While the level of oxidised to unoxidised protein can be reliably quantified by mass spectrometry (at typically between 10–30% under optimal conditions for footprinting experiments), the concentration of hydroxyl radicals in solution required to effect this has not yet been studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation